2019
DOI: 10.1002/ptr.6297
|View full text |Cite
|
Sign up to set email alerts
|

Oroxylin A, a methylated metabolite of baicalein, exhibits a stronger inhibitory effect than baicalein on the CYP1B1‐mediated carcinogenic estradiol metabolite formation

Abstract: 4-OHE2) from 17β-estradiol plays an important role in the progression of human breast cancer, while the biotransformation of 17β-estradiol to 2-hydroxyestradiol mediated by cytochrome P450 1A1 (CYP1A1) is considered as a less harmful pathway. In this study, inhibitory effects of flavonoids baicalein and oroxylin A, a metabolite of baicalein in human body, on CYP1A1 and 1B1 activities were investigated in vitro. The inhibition intensities of baicalein and oroxylin A towards CYP1B1 were greater than towards CYP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…On the other hand, it has been reported that 4-hydroxyestradiol (4-OHE2), a metabolite of estradiol, plays a critical role in the occurrence and progression of hormone-related cancers [ 19 ]. 4-OHE2 is highly carcinogenic in a variety of malignant tumors, including endometrial cancer [ 20 ] and breast cancer [ 21 , 22 ]. 4-OHE2 induces anchorage-independent growth of human mammary epithelial cells [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that 4-hydroxyestradiol (4-OHE2), a metabolite of estradiol, plays a critical role in the occurrence and progression of hormone-related cancers [ 19 ]. 4-OHE2 is highly carcinogenic in a variety of malignant tumors, including endometrial cancer [ 20 ] and breast cancer [ 21 , 22 ]. 4-OHE2 induces anchorage-independent growth of human mammary epithelial cells [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…(48) Oroxylin A Formed as a metabolite of baicalein, oroxylin A is yet another fl avonoid of high phytotherapic relevance. (49) There are published associations of the substance with the suppression of cancer via apoptosis, (50) and the study by Zou, et al (51) was the only one found that also addresses autophagy.…”
Section: Sotetsu Flavonementioning
confidence: 99%
“…13 2,4-Bis(3,5-dimethoxyphenyl)pyrimidine (11). A flask was charged with 0.2 g of 2,4-dibromopyrimidine (0.84 mmol, 1 equiv), 0.337 g of 3,5-Bis (3,5-dimethoxyphenyl)pyridine (12). A flask was charged with 0.21 g of 3,5-dibromopyridine (0.89 mmol, 1 equiv), 0.338 g of 3,5-dimethoxyphenylboronic acid (1.85 mmol, 2.1 equiv), 0.01 g of Pd(OAc) 2 (0.042 mmol, 0.05 equiv), and 0.03 g of CataCXium A (0.084 mmol, 0.01 equiv) under a flow of N 2 , and the general procedure B mentioned above was carried out.…”
Section: 3″55″-tetramethoxy-11′:2′1″-terphenyl (2)mentioning
confidence: 99%
“…In recent years, CYP1B1 has emerged as a promising therapeutic target. In addition to its well-studied role as an activator of procarcinogens, CYP1B1 is overexpressed in cancer tissues, is associated with cellular resistance to taxanes, cisplatin, and gemcitabine and is responsible for the oxidation of endogenous 17β-estradiol into the DNA-damaging agent 4-hydroxyestradiol. , Expression of CYP1B1 is also known to be induced by estrogen, resulting in a dangerous feedback loop for tissues exposed to high levels of this hormone. In addition, CYP1B1 expression is associated with poor survival in associated cancers. , Thus, highly selective inhibitors for CYP1B1 may serve multiple purposes in treating and preventing drug-resistant cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation